Bioaugmentation process for the treatment of tannery effluents in Fez, Morocco: An eco-friendly treatment using novel chromate bacteria. (December 2020) - Elkarrach, Karima; Merzouki, Mohammed; Biyada, Saloua; Benlemlih, Mohamed
Abstract: Bioaugmentation is a promising, eco-friendly, and economical technique; it also aims at enhancing the efficiency of wastewater treatments. Moreover, this technique, which is based on microorganisms, performs an important function in the removal of contaminants from water. Therefore, the main objective of this study was isolation and identification of novel bacteria responsible of chromium removal, and then the treatment of tannery effluent through this process using the isolated strains. In fact, the isolation was from a composite tannery effluent. Regarding the bioaugmentation test, tannery effluents were inoculated with biomass and were incubated at 37 °C for 30 h. A consortium and different bacterial concentrations were studied to show their effects. Throughout incubation, several samples were taken to determine the bacterial growth, total and hexavalent chromium. As a result, Bacillus.sp, Enterobactera erogenes, and Bacillus pumilus were isolated and their bioremediation capacity was shown, especially their removal capacity of chromium. Thus, these isolated strains could be novel chromium-resistant bacteria. For each strain, total chromium removal achieved 60 % using the bacterial concentration of 2%. This removal increased to 80 % with the concentration 6%. As for Cr(VI), its removal increased from 60 % to more than 96 % when the bacterial concentration increases from 2% to 6%. Otherwise, Cr (T) and Cr(VI) removals were around 60–70 % for the consortium. Consequently, the bacterial concentration 6% had a strong significant effect on chromium removals. The isolated strains had statistically the same effect on chromium removals, whereas the consortium did not have a significant effect on chromium removals.